81.3k views
4 votes
7b squared -21b-273=7

User ElArbi
by
6.1k points

2 Answers

4 votes

7b^2 -21b -273 =7

Moving the -273 to the right hand side

7b^2 -21b =7+273

7b^2 -21b =280

Dividing the whole equation by 7,thus 7b^2/7 -21b/7 = 280/7

You will get

b^2 -3b =40.

Solving the equation as quadratic by moving the 40 to left side and equating the equation to zero, thus

b^2 -3b -40 =0

Factorizing b , you will get

(b-8) and (b+5) =0 thus b=8 ,b=-5 respectively. Now substituting the -5 in the equation satisfies it. Therefore b = -5

User Todd Owen
by
5.7k points
4 votes

Answer:

Given 7b²-21b-273=7, the solutions are x1 = 8 and x2 = -5.

Explanation:

Given 7b²-21b-273=7, first you need to equal zero. So

7b²-21b-273-7=0 ⇒ 7b²-21b-280 = 0

The secon step is to find the solutions applying Bhaskara´s formula x = (-b ± √(b²-4×a×c))/2×a

Where a=7, b= -21 and c= -280

After you identified each term, you have to replace it on the formula so....

x = (21 ± √(21² - 4×7×(-280)))/2×7 ⇒ x = (21 ± √(441 + 7840))/14 ⇒ x = (21 ± √8281)/14

Then you will obtain two values for x, called x1 = 8 and x2=-5.

User Scoob
by
6.0k points